2013
DOI: 10.1371/journal.pone.0079006
|View full text |Cite
|
Sign up to set email alerts
|

A Set of Engineered Escherichia coli Expression Strains for Selective Isotope and Reactivity Labeling of Amino Acid Side Chains and Flavin Cofactors

Abstract: Biological reactions are facilitated by delicate molecular interactions between proteins, cofactors and substrates. To study and understand their dynamic interactions researchers have to take great care not to influence or distort the object of study. As a non-invasive alternative to a site-directed mutagenesis approach, selective isotope labeling in combination with vibrational spectroscopy may be employed to directly identify structural transitions in wild type proteins. Here we present a set of customized E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 66 publications
(84 reference statements)
0
26
0
Order By: Relevance
“…The presence of an unusually strong hydrogen bond donated from Tyr-21 in the signaling state of AppA was interpreted as incompatible with hydrogen bonding to the glutamine side chain amidic nitrogen (Iwata et al, 2011 ), while a previous study on TePixD concluded that both dark and light state properties of tyrosine are compatible with H-bonding to oxygen but could not fully exclude alternative orientations (Takahashi et al, 2007 ). A study on SyPixD with a different tyrosine isotope labeling pattern gave similar results and clearly showed that the structural changes are confined to the phenolic hydroxyl group without any changes to the aromatic nature of the phenyl ring (Mehlhorn et al, 2013 ).…”
Section: Bluf Photoreceptorsmentioning
confidence: 80%
“…The presence of an unusually strong hydrogen bond donated from Tyr-21 in the signaling state of AppA was interpreted as incompatible with hydrogen bonding to the glutamine side chain amidic nitrogen (Iwata et al, 2011 ), while a previous study on TePixD concluded that both dark and light state properties of tyrosine are compatible with H-bonding to oxygen but could not fully exclude alternative orientations (Takahashi et al, 2007 ). A study on SyPixD with a different tyrosine isotope labeling pattern gave similar results and clearly showed that the structural changes are confined to the phenolic hydroxyl group without any changes to the aromatic nature of the phenyl ring (Mehlhorn et al, 2013 ).…”
Section: Bluf Photoreceptorsmentioning
confidence: 80%
“…Escherichia coli CpXribF cells were transformed by electroporation with the plasmid pET11a‐CPH1‐PHR encoding amino acids 1‐504 of the plant cryptochrome from Chlamydomonas reinhardtii and an N‐terminal Strep tag II . Cells were grown in M9 minimal medium supplemented with 200 mg/L ampicillin and 50 μ m riboflavin following published procedures .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, reconstitution of photolyases or cryptochromes with FAD has been unsuccessful to date, calling for a different strategy. Recently, such an approach has been developed for heterologous expression in Escherichia coli , which includes a shutdown of the cellular riboflavin production, an enhancement of riboflavin intake by a transporter and the increase in FAD production in vivo by a bifunctional flavokinase/adenylase . Thereby, flavin at natural isotope abundance is incorporated during expression (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we present the synthesis of several flavin nucleotides isotopically labeled at the isoalloxazine core or the adenyl tail, and their utility in analyzing an intermediate of an enzymatic reaction. Isotopically labeled flavins and flavin analogues have been used in the past to probe the structural dynamics of light receptors, elucidate flavin transport and metabolism in healthy and diseased cells and gain insight into the mechanisms of flavoproteins, among other applications. In particular, reconstitution of cytochrome P450 reductase, the redox partner of P450 enzymes, with FMN analogues shed light on the mechanism of electron transfer in this protein .…”
Section: Introductionmentioning
confidence: 99%